Implementasi Cyber Public Relations Pada Media Sosial Instagram Polres Bogor - Pramudya, Dimas Adjie; Darsono, Dono; Risdayah, Enok (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
This study aims to find out and understand the process of implementing cyber public relations on the Bogor Police Instagram. The researcher describes the process of implementing social media based on the concept initiated by Regina Luttrel, namely The Circular Model Some. The stages are: the first stage is share, the second is optimized, the third is manage, and the last is engage. The paradigm used in this research is constructivism. The method used is a descriptive qualitative method using primary and secondary data sources. The data collection technique used is through passive participatory observation and in-depth interviews. The results of the research obtained from this study were the Bogor Police through its Public Relations using the model proposed by Regina Luttrell, namely The Circular Model of Some.